Control interno y el desempeño laboral de los trabajadores administrativos de la Municipalidad de San Juan Bautista en el año 2021 - Ramirez Perez, Jessy Geraldine (2023)
The present investigation sought to analyze the relationship between internal control and the work performance of administrative workers in the Municipality of San Juan Bautista during the year 2021. Through a quantitative and correlational research design, the Spearman correlation test was used to evaluate the hypotheses formulated. The results indicate a significant positive relationship between internal control, specifically in areas such as risk assessment and control activities, and the work performance of workers. These findings are consistent with previous studies carried out in different contexts, highlighting the importance of internal control not only as a supervision tool, but also as a factor influencing job performance. Based on the results obtained, a series of political recommendations are proposed to strengthen internal control practices and enhance labor performance in municipal institutions. The research contributes to academic and administrative bodies by providing a fresh perspective on how internal control can be used as an improvement tool in government settings.